PhD review: Minority voting and representation: The impact of religion, migration background and gender on voter preferences for in- and out-group politicians in France, Germany and the Netherlands (PhD by Sanne van Oosten, University of Amsterdam) - Stephens-Dougan, LaFleur (Politics of the Low Countries, 2025)
“Minority voting and representation” by Sanne van Oosten (2024) addresses the question, “Who prefers politicians with whom they share the same religion, migration background, and/or gender and why?” van Oosten offers a timely intervention into the race and ethnic politics literature, by helping us understand under what conditions voters prefer members of their in-group. While this question has been explored at length in the American context (Benjamin 2017; McConnaughy 2010) there is still much to learn.  For example, we still know very little about how in-group voting preferences operate in Europe, especially regarding the in-group voting preferences of European Muslims. We also do not know very much about the majority group’s voting preferences for Muslim politicians, as much of the study of the voting preferences of the majority group has focused on voter preferences at the party level and not at the politician level.